2009
DOI: 10.1080/15412550902724073
|View full text |Cite
|
Sign up to set email alerts
|

Formoterol and Tiotropium Compared With Tiotropium Alone for Treatment of COPD

Abstract: Combined use of beta(2)-agonists and anticholinergic bronchodilators may have complementary benefits in patients with chronic obstructive pulmonary disease (COPD). The objective of this study was to compare combination treatment with formoterol (FORM) plus tiotropium (TIO) versus treatment with TIO alone in patients with COPD. In this active-controlled, double-blind, multicenter trial, a total of 255 subjects with diagnosed COPD were randomized to 12 weeks of either a combination of FORM 12 microg twice-daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 22 publications
4
80
0
3
Order By: Relevance
“…LABA combination therapy compared with TIO monotherapy are consistent with results from several RCTs which directly compared various LAMA ? LABA therapies with TIO [14][15][16][17][18][19][20]. This observation is therefore not unexpected and could be attributed to the direct agonist effect of the added LABA, as well as possible synergistic effects [13].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…LABA combination therapy compared with TIO monotherapy are consistent with results from several RCTs which directly compared various LAMA ? LABA therapies with TIO [14][15][16][17][18][19][20]. This observation is therefore not unexpected and could be attributed to the direct agonist effect of the added LABA, as well as possible synergistic effects [13].…”
Section: Discussionmentioning
confidence: 75%
“…In the last decade, multiple randomized controlled trials (RCTs) have reported that improvements in lung function and patient-reported outcomes (PROs) can be achieved with LAMA ? LABA combinations compared with the component monotherapies for patients with stable COPD, with no differences in safety [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a growing body of evidence demonstrating the benefits of dual bronchodilation over monotherapy in a number of clinical settings [4,[9][10][11][12]41], focus is now turning to the relative benefits of different bronchodilator combinations [14]. Indirect evidence from network meta-analyses indicate an efficacy gradient within the LAMA/LABA class with respect to lung function [14,15,23], and this study, the first head-to-head study of UMEC/VI and TIO/ OLO, confirmed the results of the indirect comparisons in both an all-comer and MN population [21].…”
Section: Discussionmentioning
confidence: 99%
“…A majority of patients who receive LAMA or LABA monotherapy continue to experience ongoing moderate-to-severe dyspnea, regardless of the level of lung function impairment [6], and this symptom persistence can be associated with poor health status, as well as a higher risk for moderate and severe exacerbations and augmented disease management costs [7,8]. There is now a large body of evidence to show that LAMA/LABA combinations consistently improve lung function, breathlessness and health status with no increased incidence of adverse events (AEs), compared with either LABA or LAMA alone [4,[9][10][11][12][13][14][15]. As such, LAMA/LABA combination therapy is recommended as initial therapy in most patients with persistent COPD symptoms [1].…”
Section: Introductionmentioning
confidence: 99%